2017
DOI: 10.11648/j.ajbls.20170504.12
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge, Attitudes and Practices (KAP) Regarding Human Papilloma Virus (HPV) Among Women in Karachi, Pakistan

Abstract: Background:The burden of STIs in Pakistan is much larger than reported. Various research studies indicate that the knowledge of sexually transmitted infections (STIs) and Human Papilloma Virus (HPV) in the women is low. The objective of this study is to assess the knowledge, attitudes and practice regarding STIs, HPV and sexual behaviors of contraceptive practice among women in Karachi, Pakistan. Methods: The current study was conducted in a tertiary care hospital in Karachi from Aug 2014-Aug 2015, including 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Even though there was a higher willingness of participants to accept the vaccination, the primary complaints among participants not willing to accept the vaccination were how safe the vaccine is, in addition to the acceptability of it worldwide and the price of the vaccine. This finding is similar to a study by ( 50 ), where participants were willing to undertake the vaccination at a free cost or receives a subsidiary from the government ( 51 ). Endarti et al further showed that the knowledge of vaccine effectiveness increased the willingness of people to undertake vaccination ( 51 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even though there was a higher willingness of participants to accept the vaccination, the primary complaints among participants not willing to accept the vaccination were how safe the vaccine is, in addition to the acceptability of it worldwide and the price of the vaccine. This finding is similar to a study by ( 50 ), where participants were willing to undertake the vaccination at a free cost or receives a subsidiary from the government ( 51 ). Endarti et al further showed that the knowledge of vaccine effectiveness increased the willingness of people to undertake vaccination ( 51 ).…”
Section: Discussionsupporting
confidence: 90%
“…Among the 1,376 participants involved in this survey, 1,240 participants (90.1%) representing 456 males (33.1%) and 784 females (57.0%) were aware of the terminology "cervical cancer." When stratified by gender, women had significantly greater knowledge, compared to men in terms of "cervical cancer being common in middle age (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) females" (75.5 vs. 67.5%, respectively, p ≤ 0.001). These participants were examined further to test their knowledge on some risk factors and symptoms of cervical cancer, as presented in Tables 2-4.…”
Section: Knowledge About Cervical Cancermentioning
confidence: 99%
“…In a study conducted in Indonesia, almost all of the participants were willing to go for HPV vaccination with the most encouraging factor being the belief in the efficacy of the vaccine [24]. However, a study conducted in Karachi showed that only 37.5% were willing to accept the vaccination for themselves, among which almost half of the women believed that the cost of vaccines should be subsidized by the government [30]. These findings are strikingly similar to our study where 49% of women consented to go for vaccination if it was provided free of cost.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of awareness and practice of Pap test in our study is lower than expected, as most of the participants included in the study were from medical universities. Similarly, Ismail H et al reported that only 9% women were attending gynecology clinics for their annual gynecological examination and only 13.7% of women had Pap smear done in their life [ 11 ]. Findings of a study from India were no different where although 58.6% knew about the availability of screening tests, only 3% had opted for a Pap smear [ 12 ].…”
Section: Discussionmentioning
confidence: 99%